2008
DOI: 10.2147/cia.s3635
|View full text |Cite
|
Sign up to set email alerts
|

Medical therapy options for aging men with benign prostatic hyperplasia: focus on alfuzosin 10 mg once daily

Abstract: Lower urinary tract symptoms suggestive of benign prostatic hyperplasia (LUTS/BPH) are common in aging men and can signifi cantly affect quality of life. Men with bothersome LUTS/BPH often present with various other age-related conditions, including sexual dysfunction, heart disease, hypertension, diabetes, and the metabolic syndrome, which can complicate management decisions. Therefore, healthcare providers should be familiar with fi rst-line treatment options for LUTS/BPH and their differing safety profi les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 72 publications
0
57
1
Order By: Relevance
“…Medical therapy is usually the first-line treatment option and is indicated for patients with moderate lower urinary symptoms (patients with IPSS between 8 and 19) [4][5][6]. Medical therapies for BPH relief include alpha-blockers and 5-alpha-reductase inhibitors (5-ARI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical therapy is usually the first-line treatment option and is indicated for patients with moderate lower urinary symptoms (patients with IPSS between 8 and 19) [4][5][6]. Medical therapies for BPH relief include alpha-blockers and 5-alpha-reductase inhibitors (5-ARI).…”
Section: Introductionmentioning
confidence: 99%
“…Medical therapies for BPH relief include alpha-blockers and 5-alpha-reductase inhibitors (5-ARI). Medical therapy is indicated for patients with moderate lower urinary symptoms with no absolute surgical indications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…We measured serum HbA1c levels of ≥8% in patients with MetS; however, we randomized the patients with similar IPSS scores into groups to prevent a potential bias of selection. On the contrary, Roehrborn et al [26] found a close association of MetS components with LUTS in older men, whereas Joseph et al [30] detected that hypertension or diabetes mellitus were at a risk of moderate-to-severe LUTS. However, in a recent survey, a significant positive association was not found between MetS or IR and LUTS in men or women.…”
Section: Discussionmentioning
confidence: 96%
“…By inhibiting smooth muscle α-adrenergic receptors, the drugs relax prostatic and bladder neck smooth muscles and partially improve LUTS by relieving bladder outlet obstruction. [26] Although α-blockers have a proven role for the symptomatic treatment of LUTS, there is little evidence about their efficacy for the treatment of LUTS in men with MetS. Gökkaya et al [27] prospectively evaluated the effects of IR on the outcomes of doxazosin treatment for LUTS in 64 patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that about 90% of men between 45 and 80 years old complain of some degree of LUTS (3 mcWary). More precisely, it seems that by the age of 50 [3,4] 50% of men may show the symptoms related with BPH and in those aged above 70 years this condition is the most significant cause of bladder outflow obstruction. From the histological viewpoint, the process which starts from the transitional or periurethral zone determines hyperplasia of glandular and stromal tissue with papillary buds and increased smooth muscle, lymphocytes and ducts [5,6].…”
Section: Introductionmentioning
confidence: 99%